2010
DOI: 10.4269/ajtmh.2010.10-0116
|View full text |Cite
|
Sign up to set email alerts
|

Guaroa Virus Infection among Humans in Bolivia and Peru

Abstract: Abstract. Guaroa virus (GROV) was first isolated from humans in Colombia in 1959. Subsequent isolates of the virus have been recovered from febrile patients and mosquitoes in Brazil, Colombia, and Panama; however, association of the virus with human disease has been unclear. As part of a study on the etiology of febrile illnesses in Peru and Bolivia, 14 GROV strains were isolated from patients with febrile illnesses, and 3 additional cases were confirmed by IgM seroconversion. The prevalence rate of GROV antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 25 publications
(36 reference statements)
3
14
0
Order By: Relevance
“…Recent spread of GROV into the regions of Peru and Bolivia highlights the need for focused surveillance in these areas to monitor for continued spread of GROV into surrounding areas. This finding also appears to be consistent with serologic investigations in this area, which indicate that, whereas the virus has only recently been detected in persons in these regions ( 2 ), GROV antibody has been detected in serum samples from the population dating back to 1965 ( 10 ). …”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Recent spread of GROV into the regions of Peru and Bolivia highlights the need for focused surveillance in these areas to monitor for continued spread of GROV into surrounding areas. This finding also appears to be consistent with serologic investigations in this area, which indicate that, whereas the virus has only recently been detected in persons in these regions ( 2 ), GROV antibody has been detected in serum samples from the population dating back to 1965 ( 10 ). …”
Section: Discussionsupporting
confidence: 88%
“…Guaroa virus (GROV; family Bunyaviridae , genus Orthobunyavirus ) infection in humans frequently results in febrile illness, and limited serologic surveillance indicates that the virus infects a substantial portion of the rural population in tropical regions of Central and South America (Figure 1, panel A) ( 1 , 2 ). However, similar to the situation for many arboviruses found in the Neotropics, limited systematic surveillance for GROV in rural communities contributes to a lack of information regarding the ecology and actual effect of GROV on public health.…”
mentioning
confidence: 99%
“…This study was part of a vector ecology and arthropodborne pathogen research program designed to evaluate the threat of enzootic dengue to human and animal health in this region. The study area was selected because human cases of dengue, malaria, Guaroa, Mayaro, Oropouche, Venezuelan equine encephalitis (VEE), and a large number of fevers of unknown origin were previously reported in nearby Iquitos (Tesh et al 1999;Manock et al 2009;Aguilar et al 2010Aguilar et al , 2011a.…”
mentioning
confidence: 99%
“…More recent antibody prevalence studies on samples collected in Iquitos in 2006 demonstrated an overall GROV seroprevalence of 13% (3). The increasing seroprevalence with age suggests that transmission occurred consistently in the region over several years (3).…”
mentioning
confidence: 97%
“…Guaroa virus (GROV; order Bunyavirales, family Peribunyaviridae, genus Orthobunyavirus) (2) is a known cause of febrile illness in tropical regions of Central and South America (3). It was first isolated from asymptomatic humans in Colombia in 1956 (4) and isolated from symptomatic humans in Brazil in 1964 (5).…”
mentioning
confidence: 99%